Assessing Groundwater Potential and Suitability for Drinking and Irrigation at Federal University of Lafia, Nasarawa State, Northcentral Nigeria (Lafia Journal of Scientific and Industrial Research, 2025)
Groundwater is used in industry, agriculture, and drinking. Quality must be checked regularly. This study assessed Federal University of Lafia groundwater potential for drinking and irrigation. Fifteen groundwater samples were analyze and nine Schlumberger geo-electrical soundings were carried out. The results were compared to Water Quality Index and World Health Organization drinking water standards. IP2WIN software was used to smoothed field data for models, geo-electric layers, and sounding curves. KH, QH, H, and Q curve types were obtained. Sandstone, top soil, and sandy shale exhibit varying resistivities, indicating variation in geology. The area has high aquifer protection capacity and moderate to high water potentials. The physicochemical parameters are within WHO drinking permissible limits, except for nitrate which is above the limit. Which implies contamination. The samples are excellent source of water based on water quality index. The study uses Kelly's ratio, magnesium adsorption ratio, sodium adsorption ratio, and chloro-alkaline indices to determine their suitability for irrigation. All the samples are good for irrigation with the exception of the magnesium adsorption ratio, which indicates that samples 1, 2, 3, 4, 5, 8, 9, 10, 11, 12, 13, and 14 are above 50%, indicating a negative impact on crop yield as the soil becomes more alkaline. Based on the results, the area has high groundwater potentials but poorly good for irrigation. Therefore, isotopic and geothermal analysis of the water samples in the area is necessary, in order to ascertain the exact sources of water in the area
Keywords: Drinking; Magnesium; Index; Piper; Quality; Ration